2020
DOI: 10.1126/sciadv.abb9841
|View full text |Cite
|
Sign up to set email alerts
|

A bird’s-eye view of brain activity in socially interacting mice through mobile edge computing (MEC)

Abstract: Social cognition requires neural processing, yet a unifying method linking particular brain activities and social behaviors is lacking. Here, we embedded mobile edge computing (MEC) and light emitting diodes (LEDs) on a neurotelemetry headstage, such that a particular neural event of interest is processed by the MEC and subsequently an LED is illuminated, allowing simultaneous temporospatial visualization of that neural event in multiple, socially interacting mice. As a proof of concept, we configured our syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…For example, rats shuttle together to obtain reward in an operant task (14) and aggregate in response to predator smell or bright light (15)(16)(17). Mice aggregate in the presence of a spider-robot, and being inside the aggregation attenuates the threat-induced gamma oscillations in the amygdala (18). Prairie voles follow the leader-animal to generate a uniform response to an owl attack (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…For example, rats shuttle together to obtain reward in an operant task (14) and aggregate in response to predator smell or bright light (15)(16)(17). Mice aggregate in the presence of a spider-robot, and being inside the aggregation attenuates the threat-induced gamma oscillations in the amygdala (18). Prairie voles follow the leader-animal to generate a uniform response to an owl attack (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study (Kim et al, 2020), mice showed typical defensive responses to a spider robot by naturally responding with freezing or flight. In order to quantify these behaviors, we analyzed neural dynamics in mPFC and BLA as well as concurrent behavioral states from 8 mice (8 sessions per mouse).…”
Section: Resultsmentioning
confidence: 91%
“…However, the parallel neural mechanism underlying flight and switching between opposing actions have yet to be identified. In our previous study, we showed that a spider robot as a natural threat could induce activities in the BLA that was recorded by a wireless telemetry (Kim et al, 2020), however neither concurrently measured mPFC nor specific behavioral analysis were not performed.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, after 2 consecutive days of habituation, we tested mouse behavior in response to an intruding robot spider ( Figure 2A ). This threatening stimulus has been previously characterized in group escape behavior in rodents (Kim et al, 2020). We assessed the autonomic response to the robot spider in (n=3 mice) and found a marked increase in heart rate upon introduction of the spider, confirming the perception of threat ( Supplementary Figure 1A ; ‘Baseline’ = 555.36 ± 26.19 beats/min, ‘Spider’ = 686.43 ± 31.82 beats/min, paired Cohen’s d = 2.6 [95%CI: 2.2, 3.17], paired two-sided t-test, p = 0.03).…”
Section: Resultsmentioning
confidence: 99%